Effect of Different Denture Base Cleansers on Surface Roughness of Heat Polymerised Acrylic Materials with Different Curing Process - Degirmenci, Kubra (2020)
Avoiding biofilm formation on dentures is associated with maintaining the surface properties of acrylic-based dentures. The aim of the study is to investigate the effects of two different cleaning agents (Corega and Klorhex 0.2% chlorhexidine gluconate) on surface roughness of the denture regarding efficacy of curing procedures. A total of sixty disc-shaped specimens were prepared with two different methods as long and short curing processes. The specimens were divided into subgroups according to the immersion solutions (distilled water, Corega tablet group and Klorhex 0.2% chlorhexidine gluconate group) (n=10). The samples were kept in a solution for 8 hours per day during a month. The average Ra1 (before exposure to the cleanser agent) and Ra2 (after exposure to the cleanser agent) of each sample was measured. A two-way ANOVA and post hoc Tukey test was used for statistical analysis. The solutions significantly increased the Ra values in both acrylic groups (p<0.001). While the effect of the distilled water group was significantly lower than Corega and Klorhex in the long-term curing group (p<0.05), no significant difference was found in the short-term curing group (p>0.05). The long-term curing time is highly effective in decreasing the surface roughness of the acrylic base material.